2002
DOI: 10.1038/nsb853
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic domain structure and hypothesis for function of GIY-YIG intron endonuclease I-TevI

Abstract: I-TevI, a member of the GIY-YIG family of homing endonucleases, consists of an N-terminal catalytic domain and a C-terminal DNA-binding domain joined by a flexible linker. The GIY-YIG motif is in the N-terminal domain of I-TevI, which corresponds to a phylogenetically widespread catalytic cartridge that is often associated with mobile genetic elements. The crystal structure of the catalytic domain of I-TevI, the first of any GIY-YIG endonuclease, reveals a novel alpha/beta-fold with a central three-stranded an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
123
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(128 citation statements)
references
References 30 publications
5
123
0
Order By: Relevance
“…However, alternative schemes for making double-strand breaks in DNA have yet to be eliminated for I-TevI (21). The alternatives could perhaps be tested by examining I-TevI reactions on duplexes attached to magnetic beads, on transferring the beads from nonpermissive to permissive conditions (namely Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, alternative schemes for making double-strand breaks in DNA have yet to be eliminated for I-TevI (21). The alternatives could perhaps be tested by examining I-TevI reactions on duplexes attached to magnetic beads, on transferring the beads from nonpermissive to permissive conditions (namely Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The intron-encoded endonuclease I-TevI is a monomer with one active site and it has been suggested that, after it has cleaved the bottom strand, it distorts the DNA to access the top strand (20). However, this scheme has yet to be confirmed: given the crystal structure of the catalytic domain of I-TevI, both transient dimerization and hairpin schemes are also possible (21).…”
mentioning
confidence: 99%
“…However, several active GIY-YIG ENs (i.e., all Seg proteins) do not contain either motif B with the invariant Arg or any other positively charged amino acids in this region, which argues against the indispensable role of this Arg (16,33). The neighboring highly conserved H761 may be involved in catalysis instead, as suggested for I-TevI (17).…”
Section: Discussionmentioning
confidence: 90%
“…Notably, helix 1 exhibits a strong positive charge in both molecules, with side chains of five lysine residues exposed on the surface of the Penelope EN. This feature is thought to be responsible for interaction with DNA through phosphate backbone contacts (17). The conserved N816 at the C terminus is able to form hydrogen bonds with I747 in the backbone of ␤-strand 2, thus, possibly keeping helix 3 in place.…”
Section: Sequence Conservation Of Rt and En Domainsmentioning
confidence: 99%
See 1 more Smart Citation